Diabetes mellitus, insulin, and melioidosis in Thailand. - Simpson, A; Newton, P; Chierakul, W; Chaowagul, W; White, N (2003)
A review of case records for 1817 Thai patients with melioidosis revealed that <10% of the 382 patients with diabetes mellitus were insulin dependent. This provides evidence against the hypothesis that insulin deficiency contributes to the known susceptibility to melioidosis in patients with diabetes mellitus.